Answer:
-25/12
Step-by-step explanation:
Given expression:
[tex]\bullet \ \ \dfrac{-1}{3} + \huge\text{(}\dfrac{-7}{4} \huge\text{)}[/tex]
Open the parenthesis:
[tex]\implies \dfrac{-1}{3} + \huge\text(\dfrac{-7}{4} \huge\text)[/tex]
[tex]\implies \dfrac{-1}{3} - \dfrac{7}{4}[/tex]
Make common denominators:
[tex]\implies \dfrac{-1 \times 4}{3 \times 4} - \dfrac{7 \times 3}{4 \times 3}[/tex]
[tex]\implies \dfrac{-4}{12} - \dfrac{21}{12}[/tex]
Subtract the fractions:
[tex]\implies \boxed{\dfrac{-25}{12}}[/tex]